Improving Building Longevity, Adaptability, and Sustainability: Examination of Multi-Unit Residential Building Regulations in Taiwan - Yi-kai Juan; Yu-Ching Cheng (Salehan Institute of Higher Education, 2018)
Effectively enhancing buildings’ adaptability, extending their service lives, and reducing construction wastes has become a crucial issue in the construction industry. As the transformation of the socio-economic structure and diversification of user demands has grown, occupants in residence may have various needs in different stages, rethinking a sustainable and flexible living space has received substantial focus. “Open building (OB)” is an innovative method to accommodate various changeable occupant spaces, decrease the waste caused by space adjustment and reduce maintenance costs. Although the concept of OB is beneficial for sustainable built environments, the promotion of OB in Taiwan is constrained. One of the obstacles is that the OB approach is partly in conflict with the current building regulations. Without legally developed policies, developers are reluctant to supply OB housing in the market; occupants are unwilling to take the risk of implementing OB approaches in renovation. This study applied a Kano two-dimensional quality model to classify and prioritize OB regulation suggestions proposed by experts in Taiwan. A series of forums and interviews were conducted to develop OB regulations. Barriers and challenges will be discussed for further OB development that can be applied to improve building longevity, adaptability, and sustainability.